A study on the proficiency of archivists in Metro Manila - Reyes, Raymond M.; Golfo-Barcelona, Mary Grace P.; Obille, Kathleen Lourdes B. (Quezon City School of Library and Information Studies, University of the Philippines, Diliman, 2019)
The importance, power, and values that archives hold demand qualified and competent archivists to handle them. To determine the qualified and competent archivists, it is imperative to measure their proficiency against the competency standards. Ensuring that archivists are proficient enough is a way to make sure that archives are well-protected and their power not abused.

This studied the relationship between the proficiency level of archivists in Metro Manila and their socio-demographic characteristics and the effect of the behavioral factors on this relationship. This used a three-part Survey Questionnaire to identify the archivists’ proficiency level in each of the competencies set by the International Council on Archives (ICA), their socio-demographics, and the effects of the theory-based behavioral factors. A total of 79 archivists responded, satisfying the 68 sample size generated through the Estimated Population Proportion. The analysis showed that the majority of the archivists are significantly competent only in two (Integrity and External Communication) out of 15 competencies. Archivists identified intention, motive, and attitude as the most influential factors affecting their level of proficiency. There is a weak correlation between proficiency and length of service or practice; income has a weak to moderate effect on proficiency; length of service also showed a weak association with archivist’s proficiency. When the behavioral factors are taken into account, the length of service can no longer affect the archivist’s proficiency. On the other hand, the chance of having a high level of proficiency over having a low level of proficiency increases or multiplies for every increase in income given the intervening or mediating variables (behavioral factors).

With these findings, it is recommended that a training program with appropriate weight not only on technical skills and academic competencies provided by ICA but also on the underlying behavioral factors be developed. This research enjoins the academe to develop a similar and formal training program to attend to the competency gaps. This will further help the Filipino archivists cope with the international competency standards. As an attempt to identify the proficiency level of archivists and its relationship to their socio-demographic characteristics, this research hopes that further studies be conducted about the association of other factors with the archivists’ proficiency level.
Thesis
Keywords: Archivists -- Philippines -- Manila Metropolitan Area